The profundity of mental health during the COVID-19 pandemic - Singh, Avilasha (Journal of Kathmandu Medical College, 2021)
Mental health has always been stigmatised and overlooked. Since, anxiety and stress are natural responses while facing a threat of new diseases. Hence, this pandemic has shown us the importance of mental health. During this time there have been many triggers that have caused repercussions in people’s mental health. Mental health crisis is on the rise. So, it is important to be able to tackle mental health problems as effectively as physical health problems, not only now but in the future as well, once and for all.